DERIVADAS PARCIALES .

LARORATORIO N° 2

1) Y=

π

w

cos v

,w=

1
θ

, v=

,

θ

= √θ

Solución:
y=

π

cos

1

√x

dy
dx

d √x
dx
d π w d cos v dv
¿
( )¿
dw
dv

=(

=
=

(

π w ln π

π

cos

1

√x

2)y= √ z ,z=

)

sin v

(-

ln π

.
ln θ

,

(
θ

)

−1
θ2

)(
sin v

)(

)(
1
θ2

1
2√x

)(

= w+1, w=

solución:
y=

x+ 1
ln ¿
¿
ln ¿
√¿
dy
dx

=(

d √ z d ln θ d ( w+1 ) d ln x
¿(
)(
)(
)
dz

dw
dx

1

=

2√z
¿

)

=

x+ 1
ln ¿
¿
ln ¿
√¿
1
¿

)(

1
( )
θ

(1) (

1
ln x +1

)(

1
x

)

1
x

)

)
1
2√x
ln x

)

= cos v . v= 2 x solución: y= 2 √ 1 cos 2 x dy dx 1 d √w θ d cos v d 2x ¿( )( )( ) dw dθ dv dx d =( 1 = 2 √w ¿ 1 (cos 2 x )2 1 ¿¿ 1 2 cos 2x =( 4) y= ln z −1 θ2 ¿¿ √ cos w . ln 2 . ln 2 θ ) = √x + x . . z= solución: y= ¿ cos 2√ x +x ¿ ln¿ ) )(- sin v )( sin 2x . w = θ θ .1 3) y= √w . w= ) 2x ) 2 ¿ 2θ x .

z= cos θ .w= √ m . sin 2√ x+ x )( ln 2 )( 2√ x+ x 1 +1) 2√x .h= +1) . ln 2 )( 1 2√x ) ¿ log 2 ¿ solución: hacemos y= : log 2 z . θ = ln w . m= 1 h sin x por lo tanto dy dx = = 1 d d log 2 z d cos θ d ln w d √ m h d sin x ( )( )( )( )( )( ) dz dθ dw dm dh dx 1 z ln 2 (- sin θ ) 1 w ¿ )( 1 2 √m )(- 1 h2 )( cos x ) .dy dx d ln z d cos w d 2θ ( √ x + x) dz dw dθ dx = 1 z = =- cos ln ( 5) y= √ (- sin w 1 cos 2√ x+ x ( 1 ) sin x )( 2θ .

) =( 1 w d π v d √ m d 1−x ¿( )( )( ) dw dv dm dx d .v= √ m . v=1-t . w= √ v . ln 2 . x−cos x 2 x 1 . m = 1-x . √ cos x 2 1− x sin x . 1− 1 ln 2 cos x x 2 √v ) (-1)( −sin x .1 = cos x √ sin ln( ( 1 (cos ln( )) ln2 sin x √ 1 1 ) sin x ) 2 √ 1 sin x ¿ )( x sin ¿ ¿ ¿ ¿ 1 ¿ )( ) √ 6) y= 2 1− cos x x solución : 2w hacemos : y= .w= π v por lo tanto dy dx . x +cos x x2 ¿ ) 1 π √ 1−x solución: hacemos : y= 1 w . t= cos x x por lo tanto: cos x x dx w d2 d v d 1−t ¿ ( √ )( )¿ dw dv dt d dy dx 7) y= =( = 2w = 2√ .

t= √u . n= sin t . d √ m d cos n d sin t d √ u d ln x ¿( )( )( )( ) dm dn dt du dx 1 (- sin n 1 2 √ cos sin √ ln x )( ( 2 √u cos t ¿ ¿ )( sin sin √ ln x 1 x ). 1 2 √m ln π )(-1) )( 1 2 √ 1−x ) y= √ cos sin √ ln x solución: hacemos : y= √ m .1 = ( w2 = 8) )( 1 (π π v ln π ( √1− x 2 ) π √ 1− x )( .( ) cos √ ln x )( 1 2 √ ln x )( . m = u = ln x por lo tanto : dy dx = ( = =1 x ) 1 2 √m cos n .